Empowerment of Pregnant Women in the Use of Lemongrass Plants as an Effort to Prevent Hypertension in Pregnancy in the Working Area of the Al-Aqsa Mosque Posyandu Sentani in 2023 - Astutik, Eftyaningrum Dwi Wahyu; Pratami, Yustika Rahmawati; Handayani, Endah Purwanti; Putri, Harlinda Widia (Universitas Malahayati Lampung, 2024)
ABSTRACT Hypertension in pregnancy (HDK) is one of the health problems, especially in the world of obstetrics which is still a top priority to be resolved immediately because it is a direct cause of death in mothers. The purpose of this service is to increase the knowledge of pregnant women in preventing hypertension in pregnancy. The methods used are conducting site surveys, identifying problems, planning activities, managing permits, implementing and evaluating activities. Promotional media given to respondents are banners and leaflets. The results of service activities showed an increase in adolescent knowledge after being given counseling materials related to HIV/AIDS. The conclusion of this community service activity is in the form of efforts to prevent hypertension in pregnancy so that later it can be implemented independently by pregnant women in their respective places. Keywords: Knowledge, Pregnant Women, HDK, Lemongrass Plant